Awareness of zakat distribution by UiTM Zakat Centre among UiTM Puncak Alam Students / Muammar Mohd Khairi - Mohd Khairi, Muammar (2020)
This research is aimed to analyses the awareness Awareness of Zakat distribution by UiTM Zakat centre among students of UiTM Puncak Alam. The design of this study is quantitatively. A number of faculty ware choosen which is ACIS, Faculty of Health Science and Faculty of Business Management in UiTM Puncak Alam have been used as respondents for this research. The instrument used is a survey and set of questionnaires. This study also will create respondent profile, knowing the level of awareness and the how significant is the data when compared by gender and faculty.